Transcriptomic analysis identifies lactoferrin-induced quiescent circuits in neonatal macrophages - Eigenschink, Michael; Wessely, Isabelle; Dijmarescu, Marco; Förster-Waldl, Elisabeth; Farr, Alex; Kiss, Herbert; Berger, Angelika; Wisgrill, Lukas (Frontiers in Immunology, 2023)
Upon birth, a hitherto naïve immune system is confronted with a plethora of microbial antigens due to intestinal bacterial colonization. To prevent excessive inflammation and disruption of the epithelial barrier, physiological mechanisms must promote immune tolerance within the neonatal gut. Here, we investigated the effects of human lactoferrin (hLF), a glycoprotein highly prevalent in breast milk, on immune-homeostasis in an in-vitro model of neonatal monocyte-derived macrophages. Upon differentiation of macrophages in the presence of hLF, RNA-microarray analysis revealed a distinct transcriptional program defined by cell-cycle arrest in the G2/M phase, induction of IL-4/IL-13-like signaling, modified extracellular matrix interaction and enhanced propensity for cell-cell interaction. Moreover, near-complete abrogation of transcriptional changes induced by TLR4 engagement with LPS was observed in hLF-treated samples. The global transition towards an M2-like homeostatic phenotype and acquisition of a quiescent state upon hLF treatment demonstrates lactoferrin’s ontogenetic relevance in attenuating pro-inflammatory signaling within the developing neonatal intestine.